HOW DO KNOWLEDGE AND SELF-EFFICACY OF INTERNSHIP NURSING STUDENTS IN PERFORMING CARDIOPULMONARY RESUSCITATION? - Selly Desiani; Aan Nuraeni; Ayu Prawesti Priambodo (Belitung Raya Foundation, Indonesia, 2017)
Background: Cardiopulmonary Resuscitation (CPR) is the emergency first aid in cardiac arrest. CPR delivery is influenced by knowledge and self-efficacy. Internship students can be the first responders of cardiac arrest in hospital and they are expected having knowledge and high self-efficacy of CPR. However, there is no data on self-efficacy of internship students in performing CPR. Objective: The purpose of this research was to identify knowledge and self-efficacy of the internship students in performing CPR. Methods: The method in this research was descriptive quantitative with cross-sectional approach on 76 internship students selected by simple random sampling. Knowledge questionnaire and Resuscitation Self-Efficacy Scale instrument were used, with validity score of 0.56-0.84 (α=0.91). Data were analyzed using descriptive statistics. Results: The results showed that 49 respondents (64.5%) had moderate knowledge and 73 respondents (96.1%) had high self-efficacy. The lowest domain in the knowledge was conceptual knowledge, while in the self-efficacy were reporting, debriefing and recording. Conclusions: Therefore, it becomes important to increase the information on the conceptual knowledge as well as to enhance training on the self-efficacy domains: reporting; debriefing and recording.